The Korea image of K-pop fans - Sippala, Sofia (My University, 2020)
South Korean popular culture has gained global exposure in recent years. Korean popular music, films and television dramas are increasingly consumed by international audiences that do not seem to share any other connections to South Korea. The wave of Korean popular culture is particularly visible on social networking sites and digital media. This master’s thesis aims to find out about the images foreign fans of Korean popular culture, especially Korean pop music, have of South Korea. The fans’ media practices are also studied, as media strongly impact place image formation. This thesis focuses on the ways Korean pop music is connected to place image construction and reproduction. The data for this thesis was collected via half-structured thematic interviews with nonKorean listeners of K-pop, Korean pop music. Almost all the interviewees were western and under 30 years old. The interviews were conducted both in South Korea and in Finland. The interview data was transcribed and analysed with qualitative methods. The qualitative content analysis of the textual data was guided by the concepts of place image, place branding and media geography as well as the study objectives. The fans of K-pop consider South Korea as an independent and modern nation. The images of Korea focus on the urban and the capital of Seoul. The rapid modernisation of Korea is visible on the people, as there is a generational gap between young and old Koreans. The ideas of the masculine are different in Korea because aesthetic beauty is expected from everyone. The fans consumption of K-pop related media is focused on digital platforms. The fans are active and they form fan communities online. K-pop is seen as a highly produced genre that is controlled by large Korean entertainment companies. The companies mould the K-pop stars and music to be as commercially successful as possible. K-pop has some Korea markers, but the genre has become more placeless with the global success. The increasing placelessness of K-pop and the activity of the fans can help to deconstruct the place hierarchy of global popular culture and make it more diverse.

Eteläkorealainen populaarikulttuuri on levinnyt maailmalla viime vuosien aikana. Korealaista populaarimusiikkia, elokuvia ja televisiosarjoja kuluttaa yhä enenevissä määrin kansainvälinen yleisö, jolla ei vaikuta olevan muita yhteyksiä Etelä-Koreaan. Korealaisen populaarikulttuurin aalto on erityisen selkeästi esillä sosiaalisessa mediassa ja digitaalisilla alustoilla. Tämän tutkimuksen tavoitteena on valottaa korealaisen populaarikulttuurin ja erityisesti korealaisen pop-musiikin fanien Korea-mielikuvia ja - käsityksiä. Myös fanien mediakäytöt ovat tutkimuksen kohteena, sillä media vaikuttaa suuresti paikkamielikuvien syntyyn. Tämän tutkimuksen keskiössä on korealaisen popmusiikin yhteys paikkamielikuvien ja -käsitysten tuotantoon. Tutkimuksen aineisto on kerätty puolistrukturoiduilla teemahaastatteluilla ei-korealaisten K-pop-fanien kanssa. Lähes kaikki haastateltavat olivat länsimaisia ja alle 30-vuotiaita. Haastattelut tehtiin Etelä-Koreassa ja Suomessa. Haastatteluaineisto litteroitiin ja analysoitiin laadullisten menetelmien avulla. Tekstiaineiston laadullista sisällönanalyysiä ohjasivat tutkimuksen pääkäsitteet (paikkamielikuva, paikkamarkkinointi ja mediamaantiede) sekä tutkimustavoitteet. Fanit pitävät Etelä-Koreaa itsenäisenä ja modernina valtiona. Mielikuvat Koreasta keskittyvät kaupunkiympäristöön sekä erityisesti pääkaupunki Souliin. Korean nopea modernisaatio näkyy ihmisissä, sillä nuoria ja vanhoja korealaisia erottaa sukupolvien välinen kuilu. Maskuliinisuuden käsitykset Koreassa ovat erilaisia, sillä esteettistä kauneutta vaaditaan kaikilta ihmisiltä. Fanit kuluttavat K-poppiin liittyvää sisältöä pääosin digitaalisen median alustoilla. Fanit ovat aktiivisia ja he muodostavat faniyhteisöjä verkossa. K-poppia pidetään vahvasti tuotettuna genrenä, jota kontrolloivat suuret korealaiset viihdeyritykset. Nämä yritykset muokkaavat K-pop-tähdistä ja musiikista mahdollisimman myyvää. K-popissa on piirteitä, jotka liittävät sen Koreaan, mutta genrestä on tullut paikattomampaa globaalin menestyksen myötä. K-popin lisääntyvä paikattomuus ja fanien aktiivisuus voivat auttaa globaalin populaarikulttuurin paikkahierarkian purkamisessa sekä lisätä monimuotoisuutta.
Keywords: K-pop, Hallyu, place image, media geography